Building Community Awareness of Palliative Care through Faith-Based Education: A Muhammadiyah Engagement Model - Inggriane Puspita Dewi; Shella Febrita Putri Utomo; Ariani Fatmawati; Anggriyana Tri Widiyanti; Soviaturohmah Soviaturohmah; Resti Febriyanti (Universitas 'Aisyiyah Bandung, 2025)
Palliative care plays a crucial role in supporting individuals with chronic and life-limiting illnesses, yet awareness remains limited, especially in resource-constrained areas like Sucinaraja, Garut Regency. This community service initiative sought to increase understanding of palliative care among members of the Muhammadiyah community through a two-day educational seminar. The program covered prevalent chronic diseases, core principles of palliative care, and identification of patients needing such services. A total of 54 participants attended, engaging in interactive lectures and practical exercises. Knowledge and awareness were assessed using pre- and post-test. Results revealed substantial improvement: post-test accuracy surpassed 80% across all knowledge items, while participants’ awareness significantly increased, with most expressing strong agreement on the importance and community relevance of palliative care. Furthermore, there was notable family support for the integration of palliative care services. This program underscores the value of culturally tailored, community-based health education and the strategic role of religious organizations in promoting public health. Future programs should explore broader outreach and evaluate long-term behavioral impacts